Pengembangan Media Pembelajaran Flipbook Audio-Interaktif Sebagai Sarana Pembelajaran Tajwid Bagi Santri PPTQ Thohiron Mubarokan - Ahmad Riziq Al Khalid; Muhammad Syarif Hadiyatullah Fikri; Abdulloh Faqih; Ririn Inayatul Mahfudloh (Pascasarjana Universitas Qomaruddin, 2026)
This study aims to develop an audio-interactive flipbook learning media as a means of learning tajwid for students at PPTQ Thohiron Mubarokan. The background of this research is the limited use of tajwid learning media that is still conventional in nature, making it less engaging and not yet able to optimally support students’ independent learning. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. At the analysis stage, the needs of students and the existing conditions of tajwid learning were identified. The design and development stages resulted in an audio-interactive flipbook that presents tajwid materials through systematic explanations, attractive visual displays, and correct pronunciation audio. The research subjects were students of PPTQ Thohiron Mubarokan. Data collection techniques included observation, student response questionnaires, and documentation. Research instruments were used to assess the feasibility, practicality, and students’ responses to the developed media. The results showed that the audio-interactive flipbook learning media was categorized as very feasible and practical for use in tajwid learning. The media helped students understand tajwid materials more easily through the integration of text, images, and audio features. In addition, the use of audio-interactive flipbook media increased students’ learning motivation and learning independence. Therefore, the audio-interactive flipbook learning media can be used as an effective and innovative alternative learning medium for teaching tajwid in the pesantren environment.